2020
DOI: 10.1016/j.cej.2019.122942
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of a single char particle combustion characteristics in a fluidized bed under O2/H2O condition

Abstract: Experimental study of a single char particle combustion characteristics in a fluidized bed under O 2 /H 2 O condition, Chemical Engineering

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…However, the Na* and K* peak intensities decrease because the coal particles give rise to a volatile–char flame. This is due to the fact that the coal particles undergo homogeneous and heterogeneous reactions in the volatile–char flame, and compared with the volatile flame, the rate of the heterogeneous reaction is reduced, resulting in the absorption of more heat and a consequent decrease in temperature . Therefore, the flame temperature and alkali metal intensity have a similar trend with the increase of oxygen content because the improvement of temperature promotes the thermal excitation for the alkali metals.…”
Section: Resultsmentioning
confidence: 99%
“…However, the Na* and K* peak intensities decrease because the coal particles give rise to a volatile–char flame. This is due to the fact that the coal particles undergo homogeneous and heterogeneous reactions in the volatile–char flame, and compared with the volatile flame, the rate of the heterogeneous reaction is reduced, resulting in the absorption of more heat and a consequent decrease in temperature . Therefore, the flame temperature and alkali metal intensity have a similar trend with the increase of oxygen content because the improvement of temperature promotes the thermal excitation for the alkali metals.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, the gasification effect on char combustion weakens with decreasing temperature. In our previous work, 25,27,28 we have found that the proportion of gasification increases along with temperature, while the CO 2 concentration, fluidization number, and particle size have little effect on the gasification reaction fraction.…”
Section: Introductionmentioning
confidence: 81%
“…10 The high concentration of steam significantly affects the chemical structure and combustion reactivity. 11,12 CO 2 and H 2 O change the char structure by improving its aromatization and increasing the O-containing reactive groups, which changes the reactivity. 13,14 The chemical structure of pulverized coal changes continuously during combustion as a result of thermal effects at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…More disordered carbon is formed during the pyrolysis of coal in CO 2 than in N 2 , and new O-containing reactive groups are generated . The high concentration of steam significantly affects the chemical structure and combustion reactivity. , CO 2 and H 2 O change the char structure by improving its aromatization and increasing the O-containing reactive groups, which changes the reactivity. , The chemical structure of pulverized coal changes continuously during combustion as a result of thermal effects at high temperatures. The study of the carbon crystal structure of char in different atmospheres is useful to understand the evolution of carbon during combustion and, hence, the combustion mechanism of pulverized coal.…”
Section: Introductionmentioning
confidence: 99%